Duration of preoperative pain and return to work after lumbar microdiscectomy in a Social Security Hspital Lima, Peru - Laos-Plasier, Eduardo Jonathan (2022)
Objetive: To determine if there is a significant relationship between the duration of preoperative pain and the time to return to work in patients undergoing surgery for lumbar disc herniation. The study: Retrospective, cross-sectional and analytical study. Patients undergoing microdiscectomy due to lumbar disc herniation. The duration of preoperative pain was divided into two groups: >6 and ≤ 6 months of pain until the time of surgery. "Return to work" with a cutoff point of 3 months. SPSS program was used, OR was calculated. Findings: 68 patients were analyzed. 55.9% were operated after 6 months of symptoms, 30.9% did not return to work at 3 months after surgery. The OR for “non-return to work at 3 months” group was 3.65 (95% CI:1.14-11.5 p:0.034). Conclusions: The duration of preoperative pain and the time to return to work, in patients undergoing surgery for lumbar disc herniation, have a statistically significant relationship.